Electrocoagulación en la remoción de contaminantes de efluentes provenientes de fertilizantes nitrogenados (2018)
The fertilizer overuse joined to the urban and agricultural waste leaching has increased the nitrates presence in the water sources, wich has increased the concern due to its human and environmental health repercution. The electrocoagulation has proven to be a suitable technique for the nitrites removal presenting a series of advantages over other purification methods like the chemical coagulation, reverse osmosis, the ion Exchange and the biological treatments. This article introduces a review of the electrocoagulation technology progress, including information over the set of electrochemical reactions in the electrodes, as well as oxide - reduction electrochemical and balanced reactions within the solution. A discussion is made over the study of different variables that affect over the removal efficiency, like: current density, pH, type of electrodes, cell design and retention time, as well as a description of advantages and disadvantages of this technology. The article concludes with some general conclutions together with outlooks and approaches that, according to several authors, must be addressed in future research to empty spaces in the knowledge of this technology.